Analysis of the promotion of consumer psychological analysis and marketing to sports propaganda - Wei Cai , (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
In recent years, the number of sports enthusiasts in China has increased. Other domestic and international sporting goods manufacturers have also cited running gear as a primary development focus. The geographical environment and its environment heavily influence the marketing approach for the running brand Decay in a particular region. This study used the PEST analysis tool to investigate the region's political, economic, social, cultural, technological development, and other environmental factors. The SWOT analysis tool evaluated Decathlon's strengths, weaknesses, opportunities, and threats. This study studied Decathlon's marketing strategies from the 4P and 4C perspectives, described and assessed the emerging marketing strategies, including the tactics to encourage and inhibit its development, and offered some improvement approaches. In 2021, the Decathlon sports brand will see a growth rate of 65.69%, while in 2022, the growth rate will drastically drop to 15.69%. Even though the company's revenue growth rate has slowed, the overall profit margin has not altered substantially and has maintained at roughly 29%, demonstrating that the marketing strategy is highly significant. A sports brand's marketing plan offers more advantages than its price and channel strategies.